Short-term organic fertilizer substitution increases sorghum yield by improving soil physicochemical characteristics and regulating microbial community structure - Nie, Mengen; Yue, Guangqian; Wang, Lei; Zhang, Yizhong (Frontiers in Plant Science, 2024)
Chemical fertilizer reduction combined with organic fertilizer (organic fertilizer substitution) has a positive impact on crop productivity and sustainable development. However, the effects of short-term organic fertilizer substitution on microbial community structure and functions of sorghum rhizosphere soil and on sorghum yield remain unclear. Herein, this study investigated the short-term effects of organic fertilizer substitution on sorghum soil physicochemical properties, microbial community structure and enzyme activities using Metagenomic sequencing technology. The fertilization treatment included no fertilization (CK), pure chemical fertilizer N (CF), substitution of 25% chemical fertilizer N with organic N (NF25), substitution of 50% chemical fertilizer N with organic N (NF50), substitution of 75% chemical fertilizer N with organic N (NF75), and pure organic fertilizer N (NF100); soil samples were collected and analyzed in the flowering period of sorghum.The results showed that the suitable organic fertilizer substitution rate of sorghum field was 50%, and its yield was the highest among all treatments (9789.9 kg/hm 2 ). Compared with the CF treatment, a medium ratio (50%) of organic fertilizer substitution significantly reduced soil alkalization (by 3.05%), improved soil nutrients, enhanced soil enzyme activities, and increased sorghum yield (P < 0.05). After organic fertilizer substitution treatment, higher protein, fat, and total starch levels accumulated in sorghum grains, and the tannin content of grains decreased. The effect of organic fertilizer substitution on bacterial diversity was greater than that on fungal diversity. Among the dominant bacterial phyla, the medium ratio of organic substitution treatment significantly increased the relative abundances of Proteobacteria (by 3.57%) and Actinomycetes (by 14.94%), and decreased the relative abundances of Acidobacteria (by 5.18%) and Planctomycetes (by 7.76%) compared with no fertilization, while the dominant fungal phyla did not respond significantly to the addition of organic fertilizer. Organic fertilizer substitution also improved soil microbial metabolic pathways, biosynthesis of secondary metabolites, and carbon metabolism. The biomarkers enriched in inorganic fertilizer treatment and organic fertilizer substitution treatments had similar relevant environmental elements but reversed correlation trends. Moreover, soil Alkali-hydrolyzable nitrogen and L-leucine